A vision based inspection system using Gaussian mixture model based interactive segmentation - Aydin, Ilhan; Karaköse, Mehmet; Hamsin, Gaylan Ghazi; Akin, Erhan (Institute of Electrical and Electronics Engineers Inc., 2017)
The quality control is a very important task in industrial systems. When the quality control of a product has been made during production, the manufacturing defects will be minimized. For this purpose, automatic inspection system has been developed. In his study, a new vision based method is proposed for quality control and inspection purposes. The proposed method uses interactive segmentation which the main principle is based on Gaussian mixture models. After the current frame is segmented, some morphological operators will be applied to the segmented image in order to reduce noise. Some geometrical features are calculated and the objects are inspected according to their sizes. The efficiency of the proposed method has been ensured by using real videos. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Automatic inspection; Computer vision; Geometric features; Interactive segmentation; Quality control